Designing Standard Operating Procedure (SOP) for Office Vehicle Booking and Return at PT Surya Energi Indotama - Alya Istiana Annisa; Mukaram (Ebiz Prima Nusa, 2026)
This study aims to design Standard Operating Procedure (SOP) for the booking and return of office operational vehicles at PT Surya Energi Indotama, a solar energy company whose employees frequently undertake official travel. The absence of a formal SOP has caused several administrative problems, including inconsistent booking formats, unrecorded reservation data, disorganized documentation, and the inability to verify whether vehicles are returned on schedule. Using a qualitative descriptive approach, the study analyzed current practices, identified process gaps, and developed procedural standards grounded in administrative principles. Data were collected through observation, document review, and interviews with Human Resources and General Affairs staff responsible for vehicle management. The proposed SOP clarifies steps, assigns responsibilities, specifies documentation requirements, and incorporates simple digital tools, including Google Forms and Google Spreadsheets, to support a more systematic, paperless workflow. Implementation is expected to increase administrative efficiency, reduce booking errors, improve data accessibility, and strengthen control over vehicle utilization within the company. The SOP provides a practical model for organizations seeking low-cost digital solutions for routine operational management.